2011
DOI: 10.1111/j.1530-0277.2011.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent C57BL/6J Mice Show Elevated Alcohol Intake, but Reduced Taste Aversion, as Compared to Adult Mice: A Potential Behavioral Mechanism for Binge Drinking

Abstract: Background Binge alcohol drinking during adolescence is a serious health problem which may increase future risk of an alcohol use disorder. Although there are several different procedures by which to preclinically model binge-like alcohol intake, limited-access procedures offer the advantage of achieving high voluntary alcohol intake and pharmacologically relevant blood alcohol concentrations (BACs). Therefore, in the current study, developmental differences in binge-like alcohol drinking using a limited-acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 72 publications
(153 reference statements)
5
43
0
2
Order By: Relevance
“…This effect was robust and reliable, as higher EtOH intakes in adolescents were observed in both experiments, and is in agreement with all other drinking studies using limited-access procedures (Bell et al, 2011;Holstein et al, 2011;Moore et al, 2010). Although polydipsia (Bell et al, 2011), hyperphagia (Spear, 2000), or higher social isolation stress (Lopez et al, 2011) in adolescents could contribute to these results, we think these explanations were unlikely.…”
Section: Discussionsupporting
confidence: 91%
“…This effect was robust and reliable, as higher EtOH intakes in adolescents were observed in both experiments, and is in agreement with all other drinking studies using limited-access procedures (Bell et al, 2011;Holstein et al, 2011;Moore et al, 2010). Although polydipsia (Bell et al, 2011), hyperphagia (Spear, 2000), or higher social isolation stress (Lopez et al, 2011) in adolescents could contribute to these results, we think these explanations were unlikely.…”
Section: Discussionsupporting
confidence: 91%
“…Adolescent rats exhibited more approach behavior and less risk assessment in a novel, aversive environment and were less sensitive to the anxiogenic effects of FG-7142 and yohimbine. In addition to the reduced anxiogenic effects of multiple drugs in adolescent rats in the LD test, adolescents are less sensitive than adults to the aversive effects of many drugs in the conditioned taste aversion paradigm [20,21,6268,69,70]. Adolescent rats also have a deficit in expression of conditioned fear despite being able to retain the fear memory and express a normal freezing reaction in adulthood [71].…”
Section: Discussionmentioning
confidence: 99%
“…While there is convincing evidence from both our laboratory and others that mid-adolescents are less sensitive to CTA to ethanol than are adults (Anderson et al, 2010; Holstein, Spanos, & Hodge, 2011; Schramm-Sapyta et al, 2010; C. Vetter-O’Hagen et al, 2009), the precise ontogeny of these aversive properties has yet to be identified.…”
Section: Introductionmentioning
confidence: 87%